PENGARUH BELANJA PEMERINTAH TERHADAP TINGKAT KEMISKINAN DI KABUPATEN LOMBOK TIMUR TAHUN 2010-2018 - Ali, Muhamad; Muhammad, Farhana; Jailani, Huzain; Azmi, Muhammad Satrizal (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2020)
This study aimed at knowing   the effect of   government budget on education, health, and infrastructure sector toward poverty level in Lombok Timur, both partially and simultaneously.  This study was quantitative descriptive study.  The data of this study was the data of government budget on education, health, infrastructure, and the poverty level in Lombok Timur 2010 ? 2018 periods. The data of this study was secondary data that gained from literature study both using book, journal, and research, and the data of regional committee of central statistics. The technique of data analysis of this study was used   regression-linear-fold analysis by using SPSS.The result showed that partially the government budget on education health, and on infrastructure sector take effect significantly  toward poverty level in Lombok Timur, it proved by the significance score on each variable showed t-account   was x1 0.026, x2 was 0.001, and x3 was 0.025. It showed that the government budget increment in Lombok Timur Region toward each variables including education, health, and infrastructure sector take effect toward the decreasing of poverty level in Lombok Timur during study periods.